L'aspect linguistique des fusions-acquisitions d'entreprises - Vecchi, Dardo Mario de (Cuadernos de Lenguas Modernas.)
In the business world, mergers can also be seen as the joining of two or more "company-speaks". Contrasts between different "speaks" are brought out when the communities are together and this can be observed in the spoken and written language. This situation can be compared to that of languages in contact from the sociolinguistic and dialectological points of view. Terminology offers an adapted perspective on descriptive, historical and cultural levels.